Urban-rural polarization: Financial implications, challenges, and opportunities - Mori, Margherita (Journal of Innovation in Business and Economics, 2023)
This study endeavors to establish a conceptual framework for examining the cross-cultural issues arising from the enduring financial factors contributing to the urban-rural divide. Central to this framework is the notable disparity in available financial services between urban and rural areas. This discrepancy draws attention to the ongoing necessity to combat financial exclusion within agricultural communities. Broadly speaking, it underscores the significance of rural finance, a subset within the financial realm, as a potential means to mitigate the observed polarization. Key factors to be underscored include ongoing technological advancements driving progress in the financial sector and instilling hope in digitization as a catalyst for fostering inclusive finance.